Toward an understanding of language : Charles Carpenter Fries in perspective - Fries, Peter Howard; Fries, Nancy M. (J. Benjamins, 1985)
Charles C. Fries (1887-1967) was a major figure in American linguistics and language education during the first half of the 20th century. Theoretical innovation and practical implementation were important threads that ran throughout his work. Fries believed that the attempt to deal with practical problems was a vital part of developing linguistic theory. He spent most of his effort exploring grammar as a tool for communicating meaning. Charles C. Fries was quite influential in the development of linguistics in the United States, and yet in some ways remained outside of the mainstream of the li.
Keywords: Fries, Charles C. -- (Charles Carpenter), -- 1887-1967.; Fries, Charles Carpenter, -- 1887- -- Critique et interprétation.; Fries, Charles C. -- (Charles Carpenter), -- 1887-1967; Fries, Charles Carpenter.; Linguistics.; English language -- Study and teaching.; Linguistics; Linguistique.; Anglais (Langue) -- Étude et enseignement.; linguistics.; LANGUAGE ARTS & DISCIPLINES -- Linguistics -- Historical & Comparative.; English language -- Study and teaching; Linguistik; Englischunterricht; Aufsatzsammlung; Bibliografie; Sprachverstehen; Taalwetenschap.; Criticism, interpretation, etc.